Do all victimization types cluster?: assessing the co-occurrence of hate speech with criminal and bullying victimization at school - Kurpiel, Allison (Violence and victims, 2024)
Evidence indicates that poly-victimization relates to greater victim impacts than single-type victimization. A separate body of research finds that victimization motivated by bias is associated with elevated harm. However, little empirical work has assessed whether youth who experience biased victimization are poly-victims, and studies have not sufficiently examined the potentially deleterious effects of experiencing both types of victimization. This study uses nationally representative data to examine the prevalence of school-based crime and bullying victimization among hate speech victims. I then assess the odds of experiencing fear and avoiding places at school across victimization types. The findings reveal that a considerable number of hate speech victims are also bullied and that experiencing any two types of victimization is associated with increased odds of fear and avoidance. These results highlight the importance of targeting biased victimization in anti-bullying programming.